CRITICAL FACTORS INFLUENCING EFFECTIVE COMMUNICATION AMONG STAKEHOLDERS FOR PROJECT DELIVERY IN JIGAWA STATE - Abdullahi, Shazali; Waziri, Abdullahi Y.; Abdulwahab, A. S.; Adamu, Yakubu; Zadawa, Nafi’u (FUDMA JOURNAL OF SCIENCES, 2024)
Communication plays an important role in project delivery in terms of relationship, trust and collaboration among internal stakeholders. This research aims to examine the relationship between factors influencing effective communication among stakeholders and construction project delivery with a view of improving communication among stakeholders in construction project delivery in Jigawa State. Questionnaire was used for data collection in Dutse capital of Jigawa state, various factors influencing effective communication among stakeholders are identified from literature review, experts and professionals working in public and private building project in Dutse capital of Jigawa state were selected using a probability sampling technique, a total of one hundred and eight (108) respondents were selected and interviewed using structured questionnaire which represent 90% of response rate. The data are analyzed by descriptive (frequencies and percentage,) and inferential statistics (spear’s man correlation, ANOVA and regression coefficient) are conducted using SPSS 25 version software. The Findings shows that Leadership, trust, communication tools, communication skills, stakeholders involvement, cultural differences and communication technology have strong correlation with successful project delivery and understanding the factors influencing effective communication among stakeholders can foster better collaboration among stakeholders, minimize conflicts and disputes, and can lead to improved project outcomes, reduced delays, and increased customer satisfaction. Leadership, communication skill and communication tools have significant effect on construction project delivery. The factors influencing effective communication among stakeholders would consequently affect the performance of project delivery. These factors can be considered as the critical factors that enhance effective communication among stakeholders for successful project delivery in...
Keywords: Communication; Stakeholders; Construction; Project delivery